Evaluation of the effect of pesticides on the biological traits of Chironomus columbiensis - Montaño Campaz, Milton Leoncio (2022)
The use of pesticides such as pyrethroids, neonicotinoids and diamides in agriculture has generated a substantial change in agricultural production, but they have also generated great environmental damage, with direct and indirect effects on a wide variety of non-target organisms. These chemical compounds trigger a series of response mechanisms in organisms, which can occur at the physiological, reproductive, morphological, behavioral and genomic levels. For this reason, the objective of this thesis was to evaluate the effects of pesticides on biological traits of Chironomus columbiensis under controlled laboratory conditions, and also to evaluate biorational tools that cause less toxicological risks in the environment. To develop these objectives, four assays were carried out to evaluate the individual response mechanisms and processes that occur mainly at the physiological, reproductive and morphological levels. The first experiment (Chapter II) presents results on how sublethal exposure of immature C. columbiensis to deltamethrin intra- and transgenerationally altered reproduction and wing shape. In addition, it was evaluated whether the populations after exposure to the insecticide could show a recovery of reproduction (increase in the number of eggs per spawning) and wing shape after the elimination of deltamethrin in one or two generations. The second experiment (Chapter III) demonstrates sex-dependent changes (emergence, weight, reproduction and shape) in the adaptive responses of Chironomus columbiensis to acute and chronic sublethal exposures to imidacloprid. The third experiment (Chapter IV) we demonstrate sex-dependent changes (emergence, time to reach the adult stage, body mass, reproduction) and variations in egg and wing shape in responses of Chironomus columbiensis to sublethal exposures to chlorantraniliprole and its combination with imidacliprid. The fourth study (Chapter V) presents the results of the Chemical composition of essential oils of Siparuna guianensis and Siparuna gesnerioides and its effect on the Aedes aegypti and its predator. This work contains exclusively laboratory data, which evidences the responses of the non-target insect C. columbiensis to pesticide stressors such as deltamethrin, imidacloprid and chlorantraniliprole. The understanding the response mechanisms that occur at the individual and population level (e.g., physiology, reproduction, and morphology) is key to the population dynamics of thesenon-target aquatic insects. Our evidence highlights the need to adopt appropriate management strategies to mitigate the unwanted effects of synthetic insecticides on non-target insects.